Co-production of the car as a 'service': involving customers in the value chain. (6th February 2006) - Ansart, Sandrine; Chanaron, Jean-Jacques; Duymedjian, Raffi
This article deals with a possible scenario for the future of the automobile – thanks to the shift from an artefact vision to a service-oriented vision in which the customer might be involved as a true partner in the design of cars. This paper is therefore quite speculative, but it challenges the supposedly stabilised relationship between the OEMs and their ultimate clients.